2022
DOI: 10.3390/nu14132735
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Environment Interactions in Vitamin D Status and Sun Exposure: A Systematic Review with Recommendations for Future Research

Abstract: Vitamin D is essential for good health. Dermal vitamin D production is dependent on environmental factors such as season and latitude, and personal factors such as time spent outdoors and genetics. Varying heritability of vitamin D status by season has been reported, suggesting that gene-environment interactions (GxE) may play a key role. Thus, understanding GxE might significantly improve our understanding of determinants of vitamin D status. The objective of this review was to survey the existing methods in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A 23-80% heterogeneity in blood levels of vitamin D has been ascribed to genetic factors (13). Studies reporting varying heritability of vitamin D status by environments, such as season, have suggested that gene-environment interactions (GxE) play a key role (26).…”
Section: Discussionmentioning
confidence: 99%
“…A 23-80% heterogeneity in blood levels of vitamin D has been ascribed to genetic factors (13). Studies reporting varying heritability of vitamin D status by environments, such as season, have suggested that gene-environment interactions (GxE) play a key role (26).…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence supports GxE in skin cancer but further research is warranted. Future research on this topic would benefit from following the recommendations laid out in Dunn et al ( 2011 ) and Shraim et al ( 2022 ). In line with those recommendations, this review highlights the need for developing guidelines for GxE research and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors like sunlight exposure are known to influence VDR expression. 33 However, research often neglects these variables. Examining how these factors interact with vaccination-induced changes in VDR mRNA expression could provide insights into personalized vaccine responses.…”
Section: Environmental Factorsmentioning
confidence: 99%